Special Issue: Antifungal Agents Recently Approved or under Development - Ana Espinel-Ingroff; Eric Dannaoui (Journal of Fungi, 2021)
Many thanks to all contributors to the Special Issue on “Antifungal Agents Recently Approved or Under Development (Current Knowledge and Future Perspectives)” [...]